Absence of orbital rotation in superconducting CeCu 2Ge 2 - Rueff, Jean-Paul; Haverkort, Maurits W. (Physical review. B, Condensed matter and materials physics, 2015)
We address the recently proposed orbital transition scenario in heavy fermion compounds exhibiting two superconducting domes. Our method of choice is nonresonant inelastic x-ray scattering (NIXS) which probes charge densities and can be modeled quantitatively. Our NIXS results of CeCu2Ge2, a model system of this class of materials, are well described by considering the same sequence of orbitals at all temperatures, thus putting into question whether orbital transitions are related to the formation of the second superconducting dome. The discrepancy between experimental findings and prediction could be due to the lack of accuracy in the theoretical description of the 4f states.
Gesehen am 20.09.2017
Die Ziffer 2 ist im Titel zwei mal tiefgestellt